MODEL PENGEMBANGAN SIKAP DAN AMAL KEAGAMAAN SANTRI DI PONDOK PESANTREN NURUL HAQ SEMURUP KERINCI JAMBI - Masnur Alam (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2012)
AbstractWhen viewed from the domain of educational objectives, attitudes and deeds are important factors to be achieved in the learning process. Religious attitude is positive or negative affective level toward an object, like it or not, accept it or reject it, the feeling of pleasure or displeasure. The religious deed refers to religious deeds or practices, or commonly called worship. Islamic students are not only required to know something, but they also must address, live and practice it. Islamic boarding school, as one of Islamic education institutions, acknowledges that the mastery of science and technology in the globalization era is very important, but the development of attitudes and religious deeds are much more important. One of the development efforts that must to be done is by offering a development model of attitudes and religious deeds in Nurul Haq Islamic Boarding School, Kerinci, Jambi.AbstrakBila ditinjau dari domain tujuan pendidikan, sikap dan amal merupakan faktor penting yang ingin dicapai dalam proses pembelajaran. Sikap keagamaan merupakan tingkat afektif yang positif atau negaÂtif terhadap suatu objek, suka atau tidak suka, menerima atau menolak, rasa senang atau tidak senang. Amal keagamaan merupakan perbuatan atau praktik keagamaan, atau biasa disebut dengan ibadah. Santri tidak saja dituntut untuk mengetahui sesuatu, tetapi juga harus menyikapi, menghayati serta mengamalkannya. Pesantren sebagai salah satu lembaga pendidikan Islam, penguasaan ilmu pengetaÂhuan dan teknologi dalam era globalisasi sangat penting, tapi pengembangan sikap dan amal keagamaan jauh lebih penting. Salah satu upaya pengembangan yang harus dilakukan yaitu dengan menawarkan model pengembangan sikap dan amal keagamaan di Pondok Pesantren Nurul Haq Kerinci Jambi.